Formulation of Lerak Liquid Extract (Sapindus rarak DC.) as a Biosurfactant for Facial Soap - Ariawa, Dewi Cahayani; Suradnyana, I Gede Made; Suena, Ni Made Dharma Shantini (Jurnal Kefarmasian Indonesia, 2024)
Sodium lauryl sulfate (SLS) and sodium lauryl ester sulfate (SLES) are components that consumers avoid because they cause skin irritation due to the residue left behind. Lerak (Sapindus rarak DC) is a natural product with potential as a biosurfactant with a saponin content of 28%. The purpose of this study was to determine the suitability of Lerak extract facial liquid soap with the Indonesian National Standard (SNI) and its physical quality compared to soap products containing SLS and SLES, as well as to determine the panelist's acceptance of the Lerak facial soap through a hedonic test. The extract was prepared by ultrasonic-assisted maceration. The facial soap was made into four 100 ml size formulas with extract percentages of 5% (F1), 15% (F2), 25% (F3), and 35% (F4). Aspects studied included organoleptic, pH, specific gravity, foam stability, and total plate number (TPN), compared with SNI provisions. The hedonic test was conducted on 30 panelists aged 19-35. The results showed that the Lerak extract facial liquid soap met the physical quality standards set out in SNI. There are several differences in pH, specific gravity, and foam stability compared to the comparison soap product. Formula F1 gets the best score for color parameters, and F3 gets the best score for shape, smell, and usability parameters. Lerak fruit has the potential to be developed as a cleaning cosmetic product that is safe for the skin and environmentally friendly.